Spider-Man by Todd McFarlane the complete collection - McFarlane, Todd 1961-; Liefeld, Rob; Nicieza, Fabian 1962- (Marvel Worldwide, Inc., 2021)
"Todd McFarlane became a superstar illustrating AMAZING SPIDER-MAN, but he changed the industry forever with his next project: the 'adjectiveless' SPIDER-MAN! Taking on both writing and art duties, McFarlane ushered Peter Parker into a gritty new era - and it began with 'Torment'! When the Big Apple's streets run red with blood, the web-slinger heads into the sewers to stop the Lizard's homicidal rampage. But what is driving his old friend and foe? Plus: Ghost Rider lends a bony hand when the deranged Hobgoblin returns, the wall-crawler finds himself at the center of a clash of claws between Wolverine and Wendigo, and Pete goes back in black to face Morbius the Living Vampire! And in the ultimate nineties team-up, Spidey joins X-Force to battle the unstoppable Juggernaut!"--Provided by publisher
"Spider-Man created by Stan Lee & Steve Ditko"--Title page verso
Contains previously printed material : Spider-Man (1990) #1-14, #16; X-Force (1991) #4
Keywords: Wolverine -- Fiktive Gestalt; Spider-Man -- Fiktive Gestalt; Vampir; Comic